Students’ Difficulties in Writing Narrative Text - Agus Rofi’i (Papanda Journal of English Education, 2022)
This study aims to analyze the implementation of teaching writing, student’s difficulties and the problem solving in writing, especially in narrative text. The process of writing has four main elements as follows planning, drafting, editing and final version. This study uses a descriptive qualitative. The data collected from classroom and observation, questionnaire, and interview. The researcher observes the lecturers action including the students’ activities and response from the students toward the technique in teaching learning process. The result of the study, implementation of teaching writing narrative text is the lecturer always stimulates the students by showing picture series students to work in groups and pairs. The students’ difficulties in writing narrative text are grammar, lack of vocabulary; identify the generic structure of narrative text and the problem solving of teaching writing narrative text.